Peningkatan Kemampuan Menulis Surat Lamaran Pekerjaan Melalui Model Pemelajaran Berbasis Pengalaman Pada Siswa Kelas XII SMK Swasta As-Syifa Kisaran - Rusda Nita Nelly Manurung (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
The purpose of this study was to describe an increase in the ability to write job application letters through an experience-based learning model for Class XII students of As-Syifah Kisaran Private Vocational School. This type of research is classroom action research (PTK). The subjects in this study amounted to 30 students which were carried out in 2 cycles. Data collection techniques consist of observation and tests. The procedures used are (1) planning stage, (2) implementation, (3) observation, (4) reflection. The results of this study indicate that it can increase learning activities. this can be seen from the teacher's activities in the first cycle obtained an average of 26.4 with "enough" criteria and increased in the second cycle with an average of 32 with "good" criteria. In the student activity in the first cycle obtained an average of 27 with "enough" criteria and increased in the second cycle with an average score of 30 with "good" criteria. The results of the analysis of classical learning completeness in the first cycle of 65,52% with an average value of 70,24. In the second cycle, classical learning completeness is 83,24% with an average value of 77,42. Based on these data, classical learning completeness has increased. Thus it can be concluded that the application of the experience-based learning model can increase learning activities in learning to write student job applications in class XII of As-Syifah Kisaran Private Vocational School.